Human geography : landscapes of human activities - Fellmann, Jerome Donald; Getis, Arthur; Getis, Judith (Dubuque, IA : W.C. Brown, 1990)
This introduction to human geography focuses on culture, society, and human activity from a geographic perspective. Among the most distinctive features of the text is its well-integrated coverage of gender roles in society and culture
Includes bibliographical references and index.
Keywords: Human geography; Human ecology